PENGARUH MEDIA KARTU KATA BERGAMBAR TERHADAP KEMAMPUAN MEMBACA PERMULAAN DI SEKOLAH DASAR: KAJIAN LITERATUR SISTEMATIS - Repa Fajriyani Sunarya; Yoyo Zakaria Ansori; Dudu Suhandi Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early-stage reading proficiency constitutes a fundamental competency that elementary school students must possess. This competency holds a crucial role as it serves as the basis for strengthening literacy at the subsequent level of education. Various instructional media can be employed to support the strengthening of this ability, one of which is picture word cards. This medium helps students grasp the connection between written forms and the objects visualized through pictures. This condition makes the process of learning to read easier and more engaging. This study aims to evaluate the contribution of picture word cards to the early-stage reading proficiency of elementary school students through the application of the Systematic Literature Review (SLR) method. The research was conducted following the guidelines set out in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Data collection was carried out by searching academic articles indexed in Google Scholar, assisted by the Publish or Perish (PoP) application, within a publication range from 2024 to 2026. The selection process based on the established criteria yielded 13 articles deemed eligible for analysis. The findings indicate that picture word cards contribute positively to students' ability to recognize letters, pronounce syllables, articulate simple words, enrich vocabulary, and foster interest and motivation to learn. These findings affirm that picture word cards may be regarded as one effective teaching method to support the development of elementary school students' basic reading skills. Keywords: Picture Word Cards, Beginning Reading, Elementary School, Literacy, Systematic Literature Review.